2020
DOI: 10.48550/arxiv.2001.03775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interacting Dark Sectors in Anisotropic Universe: Observational Constraints and $H_{0}$ Tension

Abstract: The present study reveals observational constraints on the coupling between dark components of anisotropic Bianchi type I universe. We assume interaction between dark matter and dark energy and split the continuity equation with inclusion of interaction term Γ. Two scenarios have been considered (i) when coupling between dark components is constant and (ii) when it is a function of redshift (z). Metropolis-Hasting algorithm has been used to perform Monte Carlo Markov Chain (MCMC) analysis by using observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…In Ref. [639], a coupling between the dark components within an anisotropic Bianchi type I Universe is considered. A fit of this model to Planck 2018 + CC data gives H 0 = 65.82 +0.…”
Section: Interaction In the Anisotropic Universementioning
confidence: 99%
“…In Ref. [639], a coupling between the dark components within an anisotropic Bianchi type I Universe is considered. A fit of this model to Planck 2018 + CC data gives H 0 = 65.82 +0.…”
Section: Interaction In the Anisotropic Universementioning
confidence: 99%
“…Such an approach is studied for an "effective" curvature type contribution arising from matter clumping in [28]. Approaches based on more explicit breaking of isotropy can be found in [29].…”
Section: Subverting the Spatially Flat Frw Frameworkmentioning
confidence: 99%
“…It has been shown that some of the interacting dynamical dark energy models available on the market could be employed to solve the issue. But also, a modification of General Relativity may well lead to other solutions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] (to mention some references).…”
Section: Introductionmentioning
confidence: 99%